Pengaruh Pendidikan Pengguna Terhadap Pemanfaatan Layanan Perpustakaan di Perpustakaan Universitas Udayana - Tamara Dewi, Ni Putu Yunia; Haryanti, Ni Putu Premierita; Kastawa, Made (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2016)
ABSTRACT User education is an activity which is important to do for a library. This study aims to determine whether there is affect between user education to the utilization of library services at Library of Udayana University. The library has a complete enough facilities which is supported by user education to educate academic community of Udayana University in order to utilize the facilities and services available effectively and efficiently. This study discusses the affect of user education to the utilization of library services at Library of Udayana University which are using descriptive method and quantitative approaches. The data sources in this study derived from articles in journals, textbooks, websites, previous studies, questionnaires, direct observation and interviews. The techniques of data analysis used in this research are using validity test, reliability test, simple linear regression analysis and t test using SPSS (Statistical Package of Social Science). The results of this study state that there is a significant relationship between user education to the utilization of library services at Library of Udayana University. Keywords: User Education, Service, Collage Library